2012
DOI: 10.1002/cssc.201200780
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Carbide Nanoparticles as Efficient Cocatalysts for Photocatalytic Overall Water Splitting

Abstract: Tungsten carbide exhibits platinum-like behavior, which makes it an interesting potential substitute for noble metals in catalytic applications. Tungsten carbide nanocrystals (≈5 nm) are directly synthesized through the reaction of tungsten precursors with mesoporous graphitic C(3)N(4) (mpg-C(3)N(4)) as the reactive template in a flow of inert gas at high temperatures. Systematic experiments that vary the precursor compositions and temperatures used in the synthesis selectively generate different compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
165
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(177 citation statements)
references
References 58 publications
6
165
0
Order By: Relevance
“…Indeed, contact between TiN nanoparticles and conductive substrates has been found to be very effective in ensuring high electrochemical performance. 21 On the other hand, the crystallite particle sizes were in good agreement with the sizes estimated from XRD (typically 5-10 nm). It can be observed that the synthesis under NH 3 flow decreased the amount of amorphous species seen in the TEM image of the sample (Figure 3).…”
supporting
confidence: 73%
“…Indeed, contact between TiN nanoparticles and conductive substrates has been found to be very effective in ensuring high electrochemical performance. 21 On the other hand, the crystallite particle sizes were in good agreement with the sizes estimated from XRD (typically 5-10 nm). It can be observed that the synthesis under NH 3 flow decreased the amount of amorphous species seen in the TEM image of the sample (Figure 3).…”
supporting
confidence: 73%
“…While it can be difficult to directly benchmark catalytic performance against literature reports, these overpotentials compare favorably with those of other tungsten-based HER electrocatalysts at similar mass loadings in acidic media. For example, current densities of À10 mA cm À2 have been produced by exfoliated WS 2 nanosheets, 14 WC nanoparticles, 20 and W 2 N nanorods 16 with overpotentials of approx. À220 mV, À125 mV, and À500 mV, respectively.…”
mentioning
confidence: 99%
“…Several newer methods involve mixing a metal precursor with a carbon precursor and applying conventional and unconventional heating techniques. [11][12][13][14][15][16][17][18] Excess carbon is used to prevent sintering, but this excess carbon results in extensive surface carbon, making these materials not suitable for catalytic applications.…”
Section: Introductionmentioning
confidence: 99%